Analysis of the Effect of Motivation Factors and Hygiene Factors on Employee Performance with Job Satisfaction as a Mediation Factor : (Study on Employees PT. Bank Rakyat Indonesia (Persero) Tbk. Bandar Lampung Regional Office) - Marsudi, Didi; Ahadiat, Ayi; Jimad, Habibullah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
Human resources are a crucial aspect that determines the effectiveness of an organization. Therefore, the organization always needs to invest in recruiting, selecting and retaining its human resources not to impact turnover. To maintain and improve employee performance, it is necessary to ensure the fulfilment of motivational and hygiene factors and job satisfaction. This study aimed to determine the influence of motivational and hygiene factors on employees' functioning and job satisfaction as intermediaries (PT. Bank Rakyat Indonesia (Persero) Tbk Regional Office Bandar Lampung. Study participants were recruited from 470 BRI employees using proportionally stratified random and probability sampling. The data used in this study is primary data in the form of survey data. The data analysis method used is Structural Equation Model Analysis (SEM) with data-driven covariance. The results show that motivational factors have a positive and significant influence on employees' work performance. In contrast, hygiene factors positively and significantly influence work results and employee satisfaction. Average job satisfaction on performance between hygiene factors and employee job performance